Wokół ewolucji i kreacji - wstępna analiza ankiet nauczycieli i studentów - Jacek Tomczyk; Grzegorz Bugajak (Studia Ecologiae et Bioethicae)
The paper presents the results of the research which was carried out as part of the project: Current controversies about human origins. Between anthropology and the Bible. This project focuses on the supposed conflict between natural sciences and some branches of the humanities (notably philosophy and theology) with regard to the origin of man. The research was aimed at finding out whether such a conflict really exits. For one thing, we cannot exclude the possibility that these would-be controversies have no factual ground and that their significance is inflated by American popular literature. If, on the other hand, we assume that the conflict is real, it should be worthwhile examining its sources. Such an approach may prove helpful in systematising the highly emotional debates about the origin of man. One of the ways of tackling the issue was the questionnaire which was distributed among students, teachers and university professors. Our respondents represented three disciplines: theology, philosophy and the natural sciences, the paper will present selected results of the questionnaire which was addressed to a group of school teachers, whereas the responses of the students are given less attention in order to emphasise the teachers’ point of view, the teachers of religion and the natural sciences (biology, chemistry and physics) and the students of theology, philosophy and the natural sciences (specialising in biology and environment protection) were asked to fill in the form consisting of eleven questions, these questions concerned the following issues: the existence of the conflict between evolutionism and creationism, the definitions of creation and evolution, the existence of the spiritual element in man, ways of interpreting the Bible (esp. the first chapters of the Book of Genesis). Out of 1000 questionnaires sent out, we received 449, which should be considered a satisfactory number, given the fact that it was the first time this type of research was carried out in Poland.